The effect of education using booklet media on pregnant women's knowledge about Chronic Energy Deficiency (CED) - Lestari, Fuji; Triana Indrayani; Risza Choirunissa (KHD-Production, 2025)
Chronic Energy Deficiency (CED) is one of the nutritional problems in pregnant women that can harm maternal health and fetal growth. One of the causes of the high risk of CED is the low knowledge of pregnant women related to nutrition during pregnancy. Education using booklet media is considered adequate because it presents the material concisely, clearly, and illustrated, making it easier to understand. This study aims to determine the influence of education using booklet media on pregnant women's knowledge about CEDs. This Research uses a pre-experimental design with a group pretest-posttest design. The sample amounted to 25 pregnant women who were selected using the total sampling technique. Data was collected using a CED knowledge questionnaire, while data analysis was carried out univariate and bivariate using the Wilcoxon test. Before education, most (72.0%) of pregnant women's knowledge of CEDs was lacking. After education, all respondents (100%) were in the category of good knowledge. The difference in the average value of knowledge before and after education was 4.64. The results of the Wilcoxon test were obtained, p=0.000 (<0.05), which showed a significant influence of education using booklet media on increasing pregnant women's knowledge about CEDs. Education using booklet media is effective in increasing pregnant women's knowledge about CEDs. It is recommended that health workers use booklets as a routine educational medium, and further Research adds measures of attitudes and behaviors to see the long-term changes.